A Numerical Investigation on Gaseous Stratification Break-Up Phenomenon of Air Fountain Experiment by Code_Saturne - Zhang, Chunhui; Yu, Jiyang; Zhong, Xianping; Saeed, Muhammad (Frontiers in Energy Research, 2019)
Since the Fukushima nuclear power plant accident, the nuclear safety experts devote a number of efforts to explore the potential risk of hydrogen detonation and measures for the mitigation of hydrogen safety during a severe accident in the nuclear power plant. A series of experiments have been performed to investigate the behavior of hydrogen distribution during a severe accident in the nuclear power plant. This study aims to investigate the gaseous stratification break-up phenomenon in the presence of a vertical gas fountain on the top of containment using Code_Saturne. The computed results not only analyze the flow field of the gas and the density distribution in the containment, but also measure the adequacy of Code_Saturne concerning the multi-component gas flow calculation.